Impactos na cadeia de suprimentos: Os principais sistemas de TI, áreas impactadas e tendências futuras - Okano, Marcelo T.; Vendrametto, Oduvaldo; Marins, Fernando Augusto da Silva [UNESP]; Fernandes, Marcelo Eloy; dos Santos, Osmildo Sobral (My University, 2016)
The rapid evolution of information technology and the need always be available for customers and suppliers, practically makes mandatory that all companies involved in any supply chain, use the Information Technology ( IT ). The research is important because it will provide a study of what are the IT systems used to manage the supply chain and likely future trends. To achieve the objective of this work was carried out a survey of consultants and professionals in IT and supply chain who work in large companies. To collect the data needed for analysis, we used the exploratory research of a qualitative nature. The survey showed that all IT systems reported by Patterson et al. (2003 ), are used by some of the companies surveyed. The systems that are most commonly used by companies are those that provide greater operational benefits.
Impacts on supply chain: The main TI systems, impacted areas and future trends
Keywords: Information technology; IT; SCM; Supply chain management